THE INFLUENCE OF BRAND IMAGE, PRODUCT QUALITY, AND PRICE PERCEPTION ON INTENTION TO RESUBSCRIBE TO NETFLIX VIDEO ON DEMAND (VOD) SERVICE IN SURABAYA - Olczewski, Prully Stanislous; Purwanto, Sugeng (International Journal of Multidisciplinary Research and Literature, 2023)
In recent decades, technology has undergone rapid advancements, especially with the growth of the internet and telecommunications technology. One of the activities that people engage in for entertainment using the Internet is watching videos. The Internet as an entertainment medium, particularly in video streaming, has influenced changes in the communication industry, giving rise to the concept of subscription-based Video on Demand (VOD) services. This research investigates the impact of Brand Image, Price Perception, and Product Quality on the intention to resubscribe to Netflix's VOD service in Surabaya. The study was conducted with 120 respondents who met the criteria of having previously subscribed to Netflix and residing in Surabaya. The non-probability and purposive sampling methods were employed for participant selection. The analytical technique used in this research was Partial Least Square analysis. Primary data was collected through a questionnaire, with a Likert scale used to measure the variables in the study. This research indicates that Brand Image, Price Perception, and Product Quality positively and significantly influence the intention to resubscribe to Netflix's VOD service in Surabaya